CAN THE KANGURU MOTHER CARE (KMC) INTERVENTION IMPROVE BREAST MILK PRODUCTION? - Ayuda Nia (JURNAL KEPERAWATAN CIKINI, 2021)
Introduction: Babies who are hospitalized can be one of the factors causing stress for mothers because they have to be temporarily separated from the baby. Stress in mothers with these conditions can be affect breast milk production (ASI), meanwhile breast milk is very necessary for optimal baby growth and development. The purpose of this study was to identify the effect of the implementation kangaroo mother care (KMC) on increased milk production as long as the baby was hospitalized. Methods: The design of this study is qualitative with multiple case design involving three selected cases and has predefined inclusion criteria. The research was conducted from January to March 2016 at RSUPN Ciptomangunkusumo and RSAB Harapan Kita. Breast milk production was measure during the mother carrying out KMC for 3 days using an electric pump or marmet technique. Result: Furthermore, the results of expressed breast milk are recorded on the sheet provided. The results showed that there was an increase in milk production for 3 days with an average increase in milk production of 16,67-43,33 ml/day. Conclusion: KMC has a positive impact on milk production and volume, especially if the mother frequently implements PMK, so this intervention can support mothers who complain of low milk production.